СПЕЦИФИЧЕСКИЕ СТРАТЕГИИ ДЛЯ РАЗВИТИЯ ПОНИМАНИЯ ПРОЧИТАННОГО - Толеубаева, А.О. (SCIENCE and SOCIETY, 2020)
This article discusses some specific reading comprehension strategies for development students’ critical thinking. Reading is the process of acquiring and analysis some kind of information. Learning and implementing reading comprehension strategies helps students to think deeply and critically in all spheres of their life.
Keywords: reading; reading comprehension; strategy; critical thinking; development of comprehension